Corporate Social Responsibility and Firm Value: The Moderating Effect of Profitability - Fadillah, Rizki Rahma; Taufik, Taufik; Muthia, Fida (Jurnal Penelitian Ekonomi dan Bisnis, 2024)
This study focuses on the moderating effect of profitability on the relationship between corporate social responsibility and firm value. Using annual reports for 22 companies from Indonesia food and beverage sector for period of 2018 to 2020, this study demonstrate whether profitability able to act as a moderating variable using Moderated Regression Analysis. This study finds that profitability able to moderate the relationship between corporate social responsibility and firm value indicating that companies with better profitability able to implement the corporate social responsibility better which result in the increased in firm value. Keywords:Corporate social responsibility, Firm value, Profitability, MRA